EFFECT OF MONITORING AND EVALUATION ON COMPLETION OF WASTE MANAGEMENT PROJECTS FUNDED BY UNITED NATION DEVELOPMENT PROGRAMME IN KIBERA, NAIROBI CITY COUNTY IN KENYA - Thinguri, Sharon Njahira; Kihara, Dr. Allan (International Journal of Entrepreneurship and Project Management, 2017)
Purpose: Project monitoring is an on-going process while evaluation is occasional and aims at addressing relevance, effectiveness and impact of projects. The study main objective was to establish effect of monitoring and evaluation on successful completion of waste management projects funded by United Nation Development Programme in Kibera, Nairobi City County in Kenya. The study was guided by the following objectives; to establish the effect of project need assessment on successful completion of UNDP projects in Kenya, to determine the effect of project intervention design on successful completion of UNDP projects in Kenya, to assess the effect of project impact evaluation on successful completion of UNDP projects in Kenya and to examine the effects of project sustainability on successful completion of UNDP projects in Kenya. Methodology: The study used a descriptive survey research design. The study target population was program directors (10), project managers (10), and field extension supervisors (50). The study sample size was program directors 10, project managers 10, and field extension supervisors 50 who were sampled using census. The study used questionnaires for data collection that contained both open ended and close ended questions from the program directors, project managers, and field extension supervisors. Statistical package for social science (SPSS) version 22 was used for descriptive and inferential data analysis. The study used the multiple regression analysis models. The data presentation was done using charts, graph and tables. The 63% of (Program Directors, Project Managers and Project field extension supervisors) filled and returned the questionnaires. Results: The study found that monitoring and evaluation process influences successful completion of waste management projects funded by United Nation Development Programme in Kibera, Nairobi City County in Kenya. The study also found that Project Intervention Design and Project Impact Evaluation greatly influence successful completion of waste management projects funded by United Nation Development Programme in Kibera, Nairobi City County in Kenya. Conclusion and policy recommendation: The study concludes that project need assessment influences on successful completion of UNDP projects in Kenya. The study concluded that project intervention design significantly influences on successful completion of UNDP projects in Kenya. The study recommended that monitoring and evaluation influences successful completion of waste management projects funded by United Nation Development Programme in Kibera, Nairobi City County in Kenya. The study recommended that project intervention design significantly influences on successful completion of UNDP projects in Kenya to a great extent followed by project impact evaluation significantly influences on successful completion of UNDP projects in Kenya. The study recommended further research to be conducted on effect of monitoring and evaluation on successful completion of waste management projects funded by Nairobi City County Government to cover the 31.8% of the other factors. The study recommended other areas of study like effect of monitoring and evaluation process on successful completion of waste management projects funded by public private partnership. Also the study recommended further research to be conducted on using different variables.